Análise do teor de minerais de grão verde, torrado, borra e bebida de cafés cultivados em sistema orgânico e organomineral - Reis, Wagner José Villela dos (Universidade Federal de São Carlos, 2022)
Coffee's main attribute for determining marketing and price is quality. Minerals interfere with coffee quality through plant metabolism and accumulation of desirable chemical compounds related to aroma, flavor, and production of compounds that disfavor the microbial development of the beans. The objective of this work is to quantify the mineral content in coffees grown in organic and organomineral management systems. The amounts of minerals were analyzed in samples of green beans, roasted beans, lees and beverage, from coffees of the Catuaí Vermelho variety grown in both management systems in the municipality of Poço Fundo, MG. The organic plot received fertilization composed of bone meal, castor bean pie in a consortium with green manure. The organomineral plot received organomineral fertilization. For the grains, there was a significant difference in the phosphorus content between green and roasted grains and between the management systems, with higher values ​​being found in roasted and organic grains. For sludge and beverage, there was no significant difference between the management systems for any mineral. For comparisons between all types of samples, it was found that smaller amounts of minerals are found in the drink compared to other types of samples.
Analysis of the mineral content of green beans, roasted beans, grounds and beverage of coffees grown in organic and organomineral systems
Keywords: Secagem; Umidade; Análise física; Drying; Moisture; Physical Analysis; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES